BELKOVITE BA2(NB, TI)6(SI2O7)2O12. A NEW MINERAL FROM CARBONATITE OF THE VUORIYARVI PLUTON (KOLA PENINSULA) - Voloshin A.V.; Subbotin V.V.; Pakhomovskiy Y.A.; Bakhchisaraytsev A.Y.; Yamnova N.A.; Pushcharovskiy D.Y. (My University, 1990)
The mineral described here was found in a drill core, where it occurred in veins of dolomite- and calcite-containing carbonate cutting pyroxenite of the alkalic-ultramafic Vuoriyarvi pluton on the Kola Peninsula. The belkovite segregations occur in solution cavities that are produced by the dolomitization of pyrochlore-containing calcite carbonatite. The mineral is associated with magnetite, pyrochlore, pyrite, pyrrhotite, minerals of the apatite group, barite, alstonite, chlorite, and nenadkewitschite. It is formed by hydrothermal alteration of pyrochlore.